Business Judgment Rule (BJR) Principle in Relation to Corruption Offenses in Regionally Owned Enterprises - Muhammad Olik Abdul Holik; Agus Surono; Agung Iriantoro; Andi Wahyu Wibisana (Lembaga Teewan Journal Solutions, 2026)
This research examines legal protection for directors of Regional-Owned Enterprises (BUMD) through the application of the Business Judgment Rule (BJR) in the context of liability for corporate losses often associated with corruption offenses. This study aims to analyze the legal framework governing BJR in BUMD governance in Indonesia, examine director liability for corporate losses from the BJR perspective, and formulate a regulatory reform model to provide legal certainty and protection for BUMD directors. This research employs a normative juridical method using statutory, conceptual, and case approaches, supported by primary, secondary, and tertiary legal materials obtained through literature review and interviews. The findings indicate that BJR application is essential to distinguish between legitimate business risks and criminal offenses. Therefore, regulatory reform is necessary to clearly incorporate BJR principles such as good faith, due care, and rational business judgment as the basis for legal protection of BUMD directors. Such regulation is expected to enhance legal certainty, prevent criminalization of business decisions, and strengthen sound and professional governance of regional enterprises.